Carcinogenesis Associated with Toxin Nephropathy: Proposed Mediation by Phosphate Toxicity - Ronald B. Brown; John G. Mielke (Cells)
Although cancer is often considered a genetic disease, genotoxic damage to nuclear DNA caused by carcinogens is not always sufficient to stimulate cancer cell growth, suggesting that other etiological factors are involved. Indeed, many carcinogens are also nephrotoxic and can impair kidney function. In turn, impaired renal function can dysregulate serum inorganic phosphate, leading to hyperphosphatemia and excess phosphate storage in tissues, which causes phosphate toxicity. Moreover, phosphate toxicity can contribute to cancer cell growth by activating cell signaling pathways, overexpressing sodium phosphate cotransporters, and stimulating excessive RNA biogenesis and protein synthesis. The present narrative review proposes a general underlying mechanism by which phosphate toxicity mediates the association of toxin nephropathy with carcinogenesis. This proposed pathway could explain why any factor that impairs renal function, including an overload of nontoxic substances, may indirectly contribute to excess phosphate sequestration in the tumor microenvironment which stimulates cancer cellular growth. Importantly, chemotherapy agents are often nephrotoxic, and carcinogenicity associated with such nephrotoxins could explain the occurrence of second tumors in treated cancer patients. More research is needed to investigate the mediating role of phosphate toxicity in the association of toxin nephropathy with carcinogenesis.